Reliability-driven pin assignment optimization to improve in-orbit soft-error rate. (November 2020) - Aguiar, Y.Q.; Wrobel, F.; Autran, J.-L.; Leroux, P.; Saigné, F.; Pouget, V.; Touboul, A.D.
Abstract: Electronics are increasingly susceptible to energetic particle interactions within the silicon. In order to improve the circuit reliability under radiation effects, several hardening techniques have been adopted in the design flow of VLSI systems. This paper proposes a pin assignment optimization in logic gates to reduce the Single-Event Transient (SET) cross-section and improve the in-orbit soft-error rate. Signal probability propagation is used to assign the lowest probability to the most sensitive input combination of the circuit by rewiring or pin swapping. The cell optimization can reach up to 48% reduction on the soft-error rate. For the analyzed arithmetic benchmark circuits, an optimized cell netlist can achieve from 8% to 28% reduction on the SET cross-section and in-orbit soft-error rate at no cost in the circuit design area. Additionally, as the pin swapping is a layout-friendly technique, the optimization does not impact on the cell placement and it can be adopted along with other hardening techniques in the logic and physical synthesis.